Colonialism and communalism - Doss, M. Christhu, author.
1 online resource
Keywords: "Doss examines how the colonial construct of communalism through the fault lines of the supposed religious neutrality, the hunger for the bread of life, the establishment of exclusive village settlements for the proselytes, the rhetoric of Victorian morality, the booby-traps of modernity, and the subversion of Indian cultural heritage resulted in a radical reorientation of religious allegiance that created a perpetual detachment between proselytes and the 'others'. Exploring the trajectories of communalism, Doss demonstrates how the multicultural Indian society, known widely for its composite culture, and secular convictions were categorized, compartmentalized, and communalized by the racialized religious pretentions. A vital read for historians, political scientists, sociologists, anthropologists, and all those who are interested in religions, cultures, identity politics, and decolonization in modern India"--